Determination of lead concentration in water and in different organs of Carrasobarbus luteus and Cyprinus carpio Tigris River: Abdulmotalib J. Al-Rudainy1 and Sarah M. Al- Samawi2 - Al-Rudainy1, Abdulmotalib J. (The Iraqi Journal of Veterinary Medicine, 2017)
The present study was carried out during the period from November 2015 to April 2016 to determine the concentration of lead in Tigris River. A total of 75 fish of Hamri Carrasobarbus luteus and 82 specimen of common carp Cyprinus carpio were sampled at three different stations. Atomic absorption spectrometry is a technique for measuring quantities of Lead present in water and fish. The results showed that the mean concentration of lead in water more than in fish organs. Statistical analysis showed no significant differences in lead concentration between all stations. In C. luteus and C. carpio showed no significant differences in gills, muscles, liver and kidney between different length groups for each station. Length group 21- 30 cm at station 2 showed increasing differences compared with the same length group at station 1, Also C. carpio of Length group 31-40 cm at station 2 showed significantly increasing (P≤0.05) compared with the same length group at station 1. The highest concentration of lead was recorded in studied organs of C. luteus at station1as the following sequence: Gills > kidney > liver > muscles, while station 2: kidney > gills > liver > muscles, station 3 characterized as following sequence: Kidney > liver > gills > muscles. The highest concentration of lead was recorded in studied organs of C.carpio at station1as the following sequence: Gills > liver > muscles > kidney, while station 2: Gills > kidney > liver > muscles, station 3 characterized looks like a sequence of station 1 as following: Gills > liver > muscles > kidney. In conclusion, the result of the present study approved the presence of lead in the water of Tigris River and fish living inside it. In addition, the mean concentration of lead in water was more than in fish organs. The results also reported that lead concentration was higher than the allowable WHO concentration.